Editorial for Vol.32, No.4 - Alan Jović (Journal of Computing and Information Technology)
The December 2024 (Vol. 32, No. 4) issue of CIT. Journal of Computing and Information Technology brings four papers from the areas of power load forecasting, fault detection, multi-objective optimization, and information retrieval.